Multicenter assessment of the outcomes of subcutaneous ICD implantation in patients with prior or future sternotomy. Issue 2 (21st November 2022) - Al‐Kofahi, Mejalli; Adeola, Oluwaseun G.; Payne, Jason; Mohammed, Moghniuddin; Reddy, Y. Madhu; Dendi, Raghuveer; Pimentel, Rhea; Berenbom, Loren; Emert, Martin; Ramirez, Rigoberto; Noheria, Amit; Montgomery, Jay A.; et al.
Abstract: Background: The subcutaneous ICD (S‐ICD) is a viable alternative to transvenous ICD and avoids intravascular complications in patients without a pacing indication. The outcomes of S‐ICD implantation are uncertain in patients with prior sternotomy. Objective: We aim to compare the implant techniques and outcomes with S‐ICD implantation in patients with and without prior sternotomy. Methods: Multicenter retrospective cohort study including adult patients with an S‐ICD implanted between January 2014 and June 2020. Outcomes were compared between patients with and without prior sternotomy. Results: Among the 212 patients (49 ± 15 years old, 43% women, BMI 30 ± 8 kg/m 2, 68% primary prevention, 30% ischemic cardiomyopathy, LVEF median 30% IQR 25%–45%) who underwent S‐ICD implantation, 47 (22%) had a prior sternotomy. There was no difference in the sensing vector (57% vs. 53% primary, p = 0.55), laterality of the S‐ICD lead to the sternum (94% vs. 96% leftward, p = 0.54), or the defibrillation threshold (65 ± 1.4 J vs. 65 ± 0.8 J, p = 0.76) with versus without prior sternotomy. The frequency of 30‐day complications was similar with and without prior sternotomy ( n = 3/47 vs. n = 15/165, 6% vs. 9%, p = 0.56). Over a median follow‐up of 28 months (IQR 10–49 months), the frequency of inappropriate shocks was similar between those with and without prior sternotomy ( n = 3/47 and n = 16/165, 6% vs. 10%, p = 0.58). Conclusion: Implantation of an S‐ICD in patients with prior sternotomy is safe with a similar risk of 30‐day complications and inappropriate ICD shocks as patients without prior sternotomy.